Evaluation of A Simple DNA Extraction Method and Its Combination with Loop-Mediated Isothermal Amplification Assays for Rapid Plasmodium knowlesi Diagnosis - Meng-Yee Lai; Mohd Hafizi Abdul Hamid; Jenarun Jelip; Rose Nani Mudin; Yee-Ling Lau (Tropical Medicine and Infectious Disease, 2023)
The initial and vital stage in the diagnosis of malaria involves extracting DNA. The efficiency of malaria testing is restricted by the multiple steps involved in commercial DNA extraction kits. We attempted to improve an existing loop-mediated isothermal amplification (LAMP) for the detection of Plasmodium knowlesi by using a simple DNA extraction approach, making it a feasible option for mass screening. We utilized a simple nucleic acid extraction method directly from whole blood for the detection of P. knowlesi, taking only 5 min to complete. The extracted DNA was evaluated by two fluorescent-based LAMP and one colorimetric-based LAMP assay. The detection limit for both SYTO-LAMP and SYBR green-LAMP was 0.00001% and 0.0001% parasitemia, respectively. Meanwhile, neutral red-LAMP had a detection limit of 0.01% parasitemia. Combining this simple and inexpensive DNA extraction method, SYTO-LAMP could serve as an alternative molecular diagnosis for the detection of P. knowlesi and other human Plasmodium spp.